HUBUNGAN KELIMPAHAN MEGA BIVALVIA DENGAN KERAPATAN LAMUN DI PERAIRAN TELUK BALIKPAPAN KALIMANTAN TIMUR - Hesti, Dinda Putri; Irawan, Aditya; Sari, Lily Inderia (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, Mulawarman University, 2023)
The association of marine life that lives in seagrass beds is bivalves. The purpose of this study was to determine the relationship between the abundance of Mega Bivalvia and the density of seagrass in Balikpapan Bay, East Kalimantan. The research was conducted from October 2022 to January 2023. The research sites were divided into 4 stations with 3 repetitions at each station using the 50 cm x 50 cm quadrant transect method. Based on the results of the correlation test, it was shown that the density of seagrass in Balikpapan Bay was grown by species of E. acoroides and T. hemprichii. The Mega Bivalvia found consisted of 15 species namely, A. squamosus, A. antiquate, L. aurita, P. chloroticum, P. albidus, T. dentaria, G. pectinatum, A. violascens, P. consanguinues, T. muricatum, P. crassisulca, A. corbuloides, P. pellucidus, C. madecassinus and D. trunculus. The relationship between Mega Bivalve abundance and seagrass density in Balikpapan Bay waters is included in the moderate category but is not unidirectional or negative.